Kebijakan Penerbitan Sertipikat Elektronik Pada Sistem Pendaftaran Tanah di Indonesia Untuk Mewujudkan Kepastian Hukum - Esther Masri; Hirwansyah (KRTHA BHAYANGKARA, 2023)
The rapid advancement of technology and the emergence of various applications encourage everyone to take advantage of electronic-based services that aim to provide convenience for users. Everyone can access the information needed anywhere. Likewise in the land sector which has undergone digital transformation and implemented electronic-based land services in the form of electronic documents by imposing electronic land certificates regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 1 of 2021 concerning Electronic Certificates. This study aims to provide legal certainty regarding the importance of changing documents proving ownership of land rights through digitalization because of the large number of multiple certificates and the land mafia which results in land disputes. To analyze this research, the writer uses a normative juridical approach that uses a document study search from statutory regulations. The results of the research from the author that the application of electronic land certificates is carried out in stages to meet the needs of the people in Indonesia. It is hoped that electronic certificates can provide protection and legal certainty to land rights holders and be able to provide resolution to land disputes.